(untitled) (Teacher’s World: Journal of Education and Research, 2024)
In the post-pandemic era, the world simultaneously witnessed a rapid move towards technological integration and global interconnectedness, alongside social-economic disparities and setbacks. As a result of the COVID-19 pandemic, scientific progress extended beyond the healthcare industry and encompassed various domains of knowledge, including education. The pandemic accelerated the incorporation of ICT in education, an area that had lagged behind other sectors. Conversely, digital integration generates a disparity in knowledge acquisition between individuals who possess access to it and those who do not. This experience serves as a reminder that a considerable number of communities globally remain behind in terms of socioeconomic development and access to digital resources. This trend is especially evident in the global south, where the integration of numerous global educational innovations and approaches may further isolate an already marginalized community by failing to account for contextual factors. Providing this complexity of introducing innovative efforts to education, it is imperative to refocus contextual educational paradigms, employing a multimodal approach that intertwines research, innovation, technology integration, and social inclusion. The purpose of this editorial is to emphasize the importance of an all-encompassing educational approach that not only equips students for the challenges of the future but also cultivates a just, inventive, and resilient society. A total of 11 papers were selected to be published in this issue, which examines four significant domains of educational transformation: the integration of technology, innovative approaches, research in education, and the representation of perspectives from underrepresented groups in education. The increasing integration of technology in the field of education is evident in the articles that discuss ICT, media usage, and visual materials. Two papers revisit inquiry-based science instruction and school-home partnerships as educational strategies. Two publications centered on teachers’ practice and intention research and action research exemplify the recent shift towards involving teachers in research activities, both in higher education and at the classroom level. Three additional papers investigate the perspectives of students and underprivileged groups who are often overlooked in the development of education procedures and policies. This journal issue, thus, represents the current focus, endeavors, and implementation of education across several educational disciplines. Teacher’s World: Journal of Education and Research, 49 (2),9-14